Ответы и объяснения

2013-08-05T14:10:54+00:00
Помогаем:
\dfrac{b}{x-a}+\dfrac{a}{x-b}=2
При x \neq a,\ x \neq b получим
bx-b^2+ax-a^2=2(x^2-ax-bx+ab)
bx-b^2+ax-a^2=2x^2-2ax-2bx+2ab 
(a+b)x-(a^2+b^2)=2x^2-2(a+b)x+2ab 
2x^2-3(a+b)x+(a^2+b^2+2ab)=0 
2x^2-3(a+b)x+(a+b)^2=0
D=\dfrac{9(a+b)^2-8(a+b)^2}{4}=\dfrac{(a+b)^2}{4}
x=\dfrac{3(a+b)\pm |a+b|}{4}
Если a+b<0, то x=\dfrac{3a+3b-(a+b)}{4}=\dfrac{2a+2b}{4}=\dfrac{a+b}{2}
Если a+b \geq 0,  то x=\dfrac{3a+3b+(a+b)}{4}=\dfrac{4a+4b}{4}=a+b.
Боже,я благодарю Вас всей душой ^^